Leverage, governance and wealth effects of asset purchasers - Amira, Khaled; John, Kose; Prezas, Alexandros; Vasudevan, Gopala K. (Journal of Corporate Finance, 2013)
We examine a sample of 670 firms that announce asset purchases. We hypothesize that buyer announcement returns should be higher in the presence of better monitoring and better governance. Consistent with the monitoring hypothesis, we find that buyers with higher private debt make purchase decisions that increase shareholder value. Consistent with the governance hypothesis, we find that returns are higher for buyers that have lower antitakeover provisions in place. Consistent with the managerial discretion hypothesis, buyer announcement-period returns increase with buyer leverage. Consistent with the liquidity hypothesis, we find that announcement-period returns decrease with the seller's Z-score, suggesting that buyers benefit from the lower liquidity of assets sold by sellers with lower debt capacity and higher financial distress. We also find that buyer announcement-period returns are directly related to their operating performance in the post-purchase year.